QAIDAH FIQHIYYAH “LA YUNKARU TAGAYYURU AL AHKAM BI TAGAYYURI AZ-ZAMAN” (DINAMIKA PERUBAHAN HUKUM SESUAI DENGAN PERUBAHAN ZAMAN) (IBTIKAR: Jurnal Studi Islam dan Sosial, 2024)
This study aims to explain further about the principle of Islamic Laws namely La Yunkaru Tagayyuru Al Ahkam bi Tagayyuri az-Zaman”, which means the change of law is undeniable by the change of ages. This study uses the qualitative approach in explaining, exploring and analyzing in-depth the research results. The data collection technique used is a literature study. This study concludes the principle of Islamic Law “La Yunkaru Tagayyuru Al Ahkam bi Tagayyuri az-Zaman”, that the law which was ruled in syara’ or Islamic Law dominated by the Legal Verses, such as a must, an order, a prohibition, principles, which each of them is not applied to make a change of the law using any arguments. These all are beyond the instruments for implementation and actualization of the laws ruled by Allah as a ruler of the law.  In other words, the instrument to actualize the given orders and prohibitions could make the change of laws. The scope of this principle confronts uncertain thought (zanni) more than the certain thought (qat’i). The scope of certainty (qat’i) just can be done through instruments and given medium. This principle also implies the awareness of the law change to happen in a society. However it might be executed under urgent affairs and circumstance identified as primary or urgent needs (daruri)  even though the principle of secondary needs (hajiyyat) is undeniable. This principle also obviously opens the rooms of making change of Islamic laws due to good public interest and advanced benefits.